2021
DOI: 10.1212/wnl.0000000000012896
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Venous Sinus Thrombosis and Thrombotic Events After Vector-Based COVID-19 Vaccines

Abstract: Background and Objectives:There is accumulating evidence supporting an association between the “thrombosis and thrombocytopenia syndrome” (TTS) and adenovirus vector-based vaccines against SARS-CoV-2. Yet, TTS and TTS-associated cerebral venous sinus thrombosis (CVST) remain poorly characterized. We aim to systematically evaluate the proportion of CVST among TTS cases and assess its characteristics and outcomes.Methods:We performed a systematic review and meta-analysis of clinical trials, cohorts, case series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 39 publications
1
47
0
Order By: Relevance
“…The majority of VITT patients are younger than 50 years old with potential predominance of women [9] , [16] . The potential risk factors of VITT patients were analyzed, including obesity, hypothyroidism, oral contraceptives, hormone therapy among women, and infections [8] , [10] .…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of VITT patients are younger than 50 years old with potential predominance of women [9] , [16] . The potential risk factors of VITT patients were analyzed, including obesity, hypothyroidism, oral contraceptives, hormone therapy among women, and infections [8] , [10] .…”
Section: Epidemiologymentioning
confidence: 99%
“…Patients with VITT mainly present one or multiple thrombosis at unusual sites, including CVST, splanchnic venous thrombosis, arterial thromboembolism, and thrombotic microangiopathy (TMA) [2] . CVST is the most common site, occurring in more than 40% of the reported patients [3] , [4] , [5] , [6] , [9] , [16] , followed by splanchnic venous thrombosis. The most common symptom is severe headache, which worsens and is insensitive to analgesics, possibly with visual changes, nausea, and vomiting, and other symptoms include persistent abdominal pain, shortness of breath, chest pain, back pain, leg pain or swelling, petechiae, unexplained bruising or bleeding.…”
Section: Clinical Manifestations and Laboratory Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…TTS is frequently associated with cerebral venous sinus thrombosis (CVST); in fact, a new systematic review and meta-analysis published in Neurology by Palaiodimou et al 2 found that half of individuals who developed TTS after receiving a vector-based vaccine (ChAdOx1 nCoV-19 or Ad26.COV2.S) presented with CVST, and TTS-associated CVST had a pooled mortality of 38%. When considered in isolation, these statistics are worrying and could easily be misconstrued.…”
mentioning
confidence: 99%